Highly covalent molecular cage based porous organic polymer: pore size control and pore property enhancement. Issue 26 (6th June 2022) - Wang, Zhen; Liu, Yan-Qun; Zhao, Yu-Hang; Zhang, Qing-Pu; Sun, Yu-Ling; Yang, Bin-Bin; Bu, Jian-Hua; Zhang, Chun
Abstract : By utilizing the cage to framework strategy, the blocking pores of the cage itself were "turned on" to construct a highly covalent molecular cage based porous organic polymer. Abstract : It remains a great challenge to effectively control the pore size in porous organic polymers (POPs) because of the disordered linking modes. Herein, we used organic molecular cages (OMCs), possessing the properties of fixed intrinsic cavities, high numbers of reactive sites and dissolvable processability, as building blocks to construct a molecular cage-based POP (TPP-pOMC) with high valency through covalent cross coupling reaction. In the formed TPP-pOMC, the originating blocking pore channels of TPP-OMC were "turned on" and formed fixed pore channels (5.3 Å) corresponding to the connective intrinsic cavities of cages, and intermolecular pore channels (1.34 and 2.72 nm) between cages. Therefore, TPP-pOMC showed significant enhancement in Brunauer–Emmett–Teller (BET) surface area and CO2 adsorption capacity.